Dam Seepage Control Uses the Blanket Layer Method - Dyah Wahyu Apriani; Febriyanto Sulistio Chandra (Jurnal Talenta Sipil, 2023)
An analysis of the seepage occurring on the dam needs to be done to determine whether the size is safe to prevent collapse on the dam body. The blanket layer is a method used in seepage control. This study discussed the effectiveness of the blanket layer method in significantly reducing the seepage on the dam body by reviewing the significant drainage and stability against the uplift. A case study of Telagasari Flood Control Dam (Bendali), which suffered a water loss due to leakage on the sewer path, was carried out by performing several scenarios of analysis based on the modelling of the addition of the blanket layer, which resulted in a 98.97% decrease in the drain discharge that occurred against the conditions prior to the drain control.